Language preference for science and technology at tertiary level in Malaysia - Ismail, Jamali; Talif, Rosli; Abdullah, Ain Nadzimah (Journal of Modern Languages, 2017)
The purpose of the study is to investigate perceptions towards using English for science and technology among academic staff at various tertiary institutions in Malaysia. The study neither promotes the use of English on a widespread basis nor questions the status and role of the national language. Areas of focus for this study include perceptions regarding respondents' attitudes towards English and using English as a medium of instruction for science and technology at tertiary level.